Terminated students? academic performance: A preliminary assessment - Faridah B.; Noreliza A.M.; Noraini M.N.; Fadhilah A.R. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The College of Engineering in Universiti TenagaNasional aims to continuously achieve higher rate of its engineering graduates. However, the rate of students been terminated from pursuing their studies due to their failure in achieving the academic standard set by the university is a major concern. This paper is a preliminary study on the terminated students academic performance. It analyses the correlation between mathematics courses with some other early engineering courses taken by the terminated students and finds that prior qualification relates to the students general success in academics. This study also finds that the trend in the number of terminated students is decreasing over the years of study. BEIESP.